XPS Examination of the Chemical Composition of PEGMUA‐Coated Gold Nanoparticles. (11th July 2022) - Hepperle, Philine; Herman, Alexander; Khanbabaee, Behnam; Baek, Woon Yong; Nettelbeck, Heidi; Rabus, Hans
Abstract: A surface chemical analysis of 12 nm diameter gold nanoparticles (AuNPs) coated with polyethylene glycol (PEG)‐11‐mercaptoundecanoic acid (MUA) is performed by means of X‐ray photoelectron spectroscopy (XPS). For this purpose, the PEGMUA‐coated AuNPs are deposited using two different deposition techniques, drop‐casting or spin‐coating, on a thin‐film carbon substrate. The measurements show that AuNPs are present in the +I oxidation state due to the synthesis process of the coated AuNPs, and in the Au(0) oxidation state. Carbon and oxygen contaminations are detected on both the coating surface and carbon substrate. While sputtering of the sample with argon enables the removal of carbon and oxygen contaminations, it also removes part of the coating on the sample surface. The two deposition methods, however, do not cause any chemical structural changes to the nanoparticles. Abstract : Polyethylene glycol (PEG)‐11‐mercaptoundecanoic acid (MUA)‐coated gold nanoparticles are characterized using X‐ray photoelectron spectroscopy regarding their chemical composition. Analysis of the peaks shows that gold is present as gold (0) and gold (I). Carbon and oxygen contaminations are found on the sample which can be removed by sputtering. Different deposition techniques have no influence on the chemical structure of the sample.